Ex‐centric textualities and rehearsed narratives at a gender identity clinic in Brazil: Challenging discursive colonization. (12th July 2017) - Borba, Rodrigo
Abstract : Transsexuality is classified as a disorder by the Diagnostic and Statistical Manual of Mental Disorders, which shapes trans‐specific healthcare policies worldwide. This paper addresses the discursive effects the imposition of a psychiatric diagnosis impinges on the daily life of Brazilian gender identity clinics. It aims to assess the epistemological and political dynamics which make the global circulation of this manual possible and to understand the socialization trajectory that leads to the materialization of diagnostically driven, rehearsed narratives in a gender clinic in the global South. I argue that the globalization of medical epistemologies and their textualities homogenizes transsexuality and impels transsexual individuals and their doctors to engage in textually constrained interactional performances which make the construction of a trusting healthcare relationship virtually impossible. The paper, thus, discusses how a sociolinguistics from the South may contribute to foster (trans)autonomy in healthcare settings where epistemological imbalances produced by ex‐centric, globalized textualities constrain possibilities for agency. Abstract : Este artigo investiga os efeitos discursivos e intersubjetivos que a patologização da transexualidade impõe à vida diária de usuárixs trans do Processo Transexualizador brasileiro. Objetiva‐se (1) avaliar as dinâmicas epistemológicas e políticas que fazem a circulação de manuais diagnósticos produzidos no Norte global possível e (2) investigar a trajetória de socialização que leva à materialização in situ de narrativas ensaiadas cujo objetivo é a obtenção do diagnóstico de Transtorno de Identidade de Gênero/Disforia de Gênero em um serviço público de transgenitalização no Sul global. Argumenta‐se que a globalização de certas epistemologias médicas e seus padrões textuais estanques homogeneíza a transexualidade e constrange as potencialidades interacionais entre profissionais de saúde e usuárixs trans do serviço, dificultando, assim, a construção de relações de cuidado baseadas em confiança mútua. O artigo discute como uma sociolinguística do Sul, por assim dizer, pode contribuir na promoção de (trans)autonomia em contextos de saúde onde desequilíbrios epistemológicos produzidos por textualidades globalizadas e ex‐cêntricas limitam as possibilidades de agência.